2020
DOI: 10.3855/jidc.12260
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with poor clinical outcome in pyogenic spinal infections: 5-years’ intensive care experience

Abstract: Introduction: Management of pyogenic spinal infections (PSI) after the development of neurological deficit has not been specifically addressed in the literature. We aimed to describe real-life clinical outcomes of PSI in patients admitted to an intensive care unit with neurological deficit and identify factors associated with good prognosis. Methodology: Consecutive patients admitted to ICU with a possible diagnosis of spinal infection over five years’ period were included. Descriptive statistics were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…PS is recognized as a challenging disease with potentially devastating clinical consequences. 2,4,9,[11][12][13] In keeping with the literature, most of the patients were middle-aged or elderly men. [1][2][3][4][5][6][7][8][9][10][11] Other findings also described in previous studies included back pain in nearly all cases, 4,10,14 fever in about one-third of patients, 10 an increase in systemic inflammatory markers as a common feature, 5,10 and the predominance of Staphylococcus aureus among the causative agents.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…PS is recognized as a challenging disease with potentially devastating clinical consequences. 2,4,9,[11][12][13] In keeping with the literature, most of the patients were middle-aged or elderly men. [1][2][3][4][5][6][7][8][9][10][11] Other findings also described in previous studies included back pain in nearly all cases, 4,10,14 fever in about one-third of patients, 10 an increase in systemic inflammatory markers as a common feature, 5,10 and the predominance of Staphylococcus aureus among the causative agents.…”
Section: Discussionsupporting
confidence: 73%
“…Following the broad literature, our study also reported a high prevalence of residual symptoms among those recovering from infection. 5,13,18 This finding highlights that PS continues to lead to neurological sequelae, chronic pain, and long-term disability. However, its mortality has dropped over the last decades due to the wide use of antibiotics.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Comprehensive Medical Management in Pyogenic Spondylodiscitis 6 multiple comorbidities, most commonly diabetes mellitus (DM) 11 . Those over 65 years old are at a high risk of having neurological complications 12 , including those with DM and rheumatoid arthritis 13 . Other risk factors that increase mortality include end-stage renal disease that needs hemodialysis, liver cirrhosis, malignancy, infective endocarditis 11 , and chronic steroid use 3 .…”
Section: Gender and Age Distributionmentioning
confidence: 99%